A comparison of an operational wave–ice model product and drifting wave buoy observation in the central Arctic Ocean: investigating the effect of sea-ice forcing in thin ice cover - Nose, Takehiko; Rabault, Jean; Waseda, Takuji; Kodaira, Tsubasa; Fujiwara, Yasushi; Katsuno, Tomotaka; Kanna, Naoya; Tateyama, Kazutaka; Voermans, Joey; Alekseeva, Tatiana (Polar research, 2023)
A prototype OpenMetBuoy (OMB) was deployed alongside a commercial buoy in the central Arctic Ocean, north of the Laptev Sea, where there are historically no wave observations available. The inter-buoy comparison showed that the OMB measured wave heights and periods accurately, so the buoy data were used to study the predictability of a wave–ice model. The first event we studied was when both buoys observed a sudden decrease in significant wave heights Hm0, which was caused by the change of wind directions from along the ice edge to off-ice wind. The Arctic Ocean Wave Analysis and Forecast wave–ice model product (ARC MFC) underestimated the Hm0 on the account of the fetch being constrained by the inaccurate model representation of an ice tongue. The second case was an on-ice wave event as new ice formed. In this instance, the ARC MFC wave–ice model product largely underestimated the downwind buoy Hm0. Model sea-ice conditions were examined by comparing the ARC MFC sea-ice forcing with the neXtSIM sea-ice model product, and our analysis revealed the ARC MFC did not resolve thin ice thickness distribution for ice types like young and grey ice, typically less than 30 cm. The ARC MFC model’s wave dissipation rate has a sea-ice thickness dependence and overestimated wave dissipation in thin ice cover; sea-ice forcing that can resolve the thin thickness distribution is needed to improve the predictability. This study provides an observational insight into better predictions of waves in marginal ice zones when new ice forms.